2002
DOI: 10.1111/1475-5661.00065
|View full text |Cite
|
Sign up to set email alerts
|

The spatial anatomy of an epidemic: influenza in London and the county boroughs of England and Wales, 1918–1919

Abstract: From uncertain origins in the spring of 1918, an apparently new variant of influenza A virus spread around the world as three distinct diffusion waves, infecting half a billion and probably killing around 40 million people. This paper examines the spatial structure of influenza transmission during the ten-month course of the epidemic in England and Wales, June 1918-April 1919, using the weekly counts of influenza deaths in London and the county boroughs as collated by the General Register Office, London. In ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(43 citation statements)
references
References 19 publications
2
41
0
Order By: Relevance
“…Deaths were more likely to occur within the same week and a few hundred meters than expected given the underlying spatial and temporal clustering, speaking to the importance of neighborhood-level transmission even in a mobile, urban population. Previous studies found significant autocorrelation in influenza mortality across county boroughs in England and Wales (42) and provinces in Spain (20), but this study is unique in showing a spatial dependence in the spread of individual influenza cases during the 1918 pandemic.…”
Section: Discussionmentioning
confidence: 51%
“…Deaths were more likely to occur within the same week and a few hundred meters than expected given the underlying spatial and temporal clustering, speaking to the importance of neighborhood-level transmission even in a mobile, urban population. Previous studies found significant autocorrelation in influenza mortality across county boroughs in England and Wales (42) and provinces in Spain (20), but this study is unique in showing a spatial dependence in the spread of individual influenza cases during the 1918 pandemic.…”
Section: Discussionmentioning
confidence: 51%
“…The spatial spread of influenza has been much studied, particularly with respect to pandemic invasion waves (5)(6)(7)(8)(9)(10)(11). Simulation models incorporating air and surface transportation have generated important insights into the spread of influenza (6,7,10,11); however, the key underlying relationship between human movement and disease spread has not been verified across wide spatial scales nor contrasted among multiple interpandemic seasons of varying severity and viral subtype dominance.…”
Section: 3mentioning
confidence: 99%
“…Error bars for composite data points are calculated using bootstrapping methods (Efron, 1979). Our aggregation will average over spatial heterogeneities, which reflect the spatial diffusion of the pathogen (Smallman-Raynor et al, 2002;Eggo et al, 2010). However the cities that have symptom reporting data available are all located in mid-north England and have epidemics of similar timing.…”
Section: Data and Historical Contextmentioning
confidence: 99%
“…Fraser et al, 2011;Valleron et al, 2010). However the ecological conditions which gave rise to the three distinct peaks of mortality over a period of just nine months in England and Wales (Smallman-Raynor et al, 2002;Pearce et al, 2011) remain intriguing.…”
Section: Introductionmentioning
confidence: 99%